Vulnerability Assessment to Climate Change of Households from Mabacan, Sta. Cruz and Balanac Watersheds in Laguna, Philippines - Dorado, Rowena A.; Mendoza, Ma. Emilinda T.; Arias, Jaime Kim B.; Ballaran, Vicente G., Jr.; Maligaya, Hazel (2016)
The Province of Laguna has been identified as one of the most vulnerable to climate change. Despite the various efforts of the local government unit, the province still suffers massive damages brought about by typhoons, flooding and landslides. This signals the need for a better strategy to manage climate change related hazards. As a first step, it is necessary to characterize the vulnerability of households in the province. This study contributed towards this end a descriptive analysis of household exposure to impacts of climate related hazards and estimating a household's vulnerability index using the Vulnerability as Expected Poverty (VEP) approach. The mean VEP for a per capita monthly poverty threshold of US$1.25 is 37%, 41% for US$1.5 and 46% for US$2.0. Among the different sectors, those dependent on aquaculture/fishery had the highest incidence of vulnerability followed by those dependent on employment in the manufacturing sector. In terms of geographical location, households in the coastal areas were found to have the highest incidence, followed by those in the lowland and lastly those in the midland to highland areas.
Keywords: Climate change; Vulnerability assessment